A major step forward for the profession. Issue 1 (January 2022) - Johnson, Michael
Abstract : Just before the end of last year, UK optometrists took part in a course where they were trained in a number of new and advanced therapeutic techniques. The event was the first of its kind in the UK, but likely to be remembered as a watershed moment for optometry. In the first of two reviews, we hear the opening address from co-organiser of the event, Dr Michael Johnson .